THE INFLUENCE OF ONLINE READING HABIT ON READING ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL MUHAMMADIYAH 1 OF PALEMBANG - Yuliani, Sri; Barokah, Fitri (English Community Journal, 2017)
The Objective of this study was to know whether or not there is a significant influence of online reading habit on reading achievement of the eleventh grade students of Senior High School Muhammadiyah 1 of Palembang. The method of this study was Descriptive method. Next, The population of this study was all the students of the eleventh grade students of senior high school Muhammadiyah 1 of Palembang in academic years 2015/2016 consisted of 475 students. The researcher used the simple random sampling by taking five students every class. In collecting the data, the reseacher used questionnaire and reading test. In analyzing the data, the researcher applied the product moment correlation analysis and simple regression analysis in SPSS 16 software. Based on result of this study indicated that the correlation coefficient was 0.749 and the significant level was 0.01. Since the correlation coefficient obtained in this study was higher than r-table value, it was concluded that there was a correlation between studentsÃ¢â¬â¢ online reading habit and their reading achievement. While the number of significant (2-tailed) obtained was 0.001 which was less than the critical limit of ÃÂ± = 0.05, it means that there was a significant correlation between online reading habit and reading achievement. Based on the regression analysis, it was found that R2= 0.561which implied that 56.1% of the studentsÃ¢â¬â¢reading achievement was contributed by their reading habit.